Short-Term Effects of Ketamine and Isoflurane on Left Ventricular Ejection Fraction in an Experimental Swine Model. (27th June 2011) - Wessler, Benjamin; Madias, Christopher; Pandian, Natesa; Link, Mark S.
Abstract : Background . General anesthesia is an essential element of experimental medical procedures. Ketamine and isoflurane are agents commonly used to induce and maintain anesthesia in animals. The cardiovascular effects of these anesthetic agents are diverse, and the response of global myocardial function is unknown. Methods . In a series of 15 swine, echocardiography measurements of left ventricular ejection fraction (LVEF) were obtained before the animals received anesthesia (baseline), after an intramuscular injection of ketamine (postketamine) and after inhaled isoflurane (postisoflurane). Results . The mean LVEF of an unanesthetized swine was 47 ± 3%. There was a significant decrease in the mean LVEF after administration of ketamine to 41 + 6.5% (P = 0.003 ). The addition of inhaled isoflurane did not result in further decrease in mean LVEF (mean LVEF 38 ± 7.2%, P = 0.22 ). Eight of the swine had an increase in their LVEF with sympathetic stimulation. Conclusions . In our experimental model the administration of ketamine was associated with decreased LV function. The decrease may be largely secondary to a blunting of sympathetic tone. The addition of isoflurane to ketamine did not significantly change LV function. A significant number of animals had returned to preanesthesia LV function with sympathetic stimulation.